2015
DOI: 10.3109/08880018.2015.1022916
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin D Levels: Are Associated with Both Iron Deficiency and Anemia in Children and Adolescents?

Abstract: We have read, with great interest, the recent article by Lee. In this excellent study, the authors investigated the association between vitamin D deficiency and anemia in a nationally representative sample of Korean children and adolescents. They concluded that vitamin D deficiency is associated with increased risk of anemia, especially iron deficiency anemia, in healthy female children and adolescents. We appreciate and congratulate the authors for having addressed such an important issue. However, we have so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
3
1
Order By: Relevance
“…However, there are also studies showing no association with the prevalence of vitamin D in children with iron deficiency anemia. 19 In our study, no correlation was found regarding the prevalence of vitamin D in children with iron deficiency. Further studies are needed for the association between VDD and anemia.…”
Section: Resultscontrasting
confidence: 64%
“…However, there are also studies showing no association with the prevalence of vitamin D in children with iron deficiency anemia. 19 In our study, no correlation was found regarding the prevalence of vitamin D in children with iron deficiency. Further studies are needed for the association between VDD and anemia.…”
Section: Resultscontrasting
confidence: 64%
“…11 Zilli and colleagues reported that vit D deficiency is common in individuals with atrophic gastritis and a similar etiopathogenesis causes vit B12 deficiency. 12 While iron deficiency was detected in 11.8% of the cases, the prevalence of B12 deficiency was 23.4%, suggesting the presence of an absorption problem rather than a nutritional deficiency. The fact that vit D deficiency, whose immunological functions are well known, was as high as 49% in our study and that it was found to be associated with vit B12 deficiency suggests that this situation may be of autoimmune origin.…”
Section: Discussionmentioning
confidence: 91%
“…Aktaş from our country reported that there is a negative correlation between vit B12 and vit D levels in patients with autoimmune hypothyroidism 11. Zilli and colleagues reported that vit D deficiency is common in individuals with atrophic gastritis and a similar etiopathogenesis causes vit B12 deficiency 12. While iron deficiency was detected in 11.8% of the cases, the prevalence of B12 deficiency was 23.4%, suggesting the presence of an absorption problem rather than a nutritional deficiency.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation